Fast Proton Exchange in Histidine: Measurement of Rate Constants through Indirect Detection by NMR Spectroscopy. Issue 21 (9th April 2014) - Sehgal, Akansha Ashvani; Duma, Luminita; Bodenhausen, Geoffrey; Pelupessy, Philippe
Abstract: Owing to its imidazole side chain, histidine participates in various processes such as enzyme catalysis, pH regulation, metal binding, and phosphorylation. The determination of exchange rates of labile protons for such a system is important for understanding its functions. However, these rates are too fast to be measured directly in an aqueous solution by using NMR spectroscopy. We have obtained the exchange rates of the NH3 + amino protons and the labile NH ε2 and NH δ1 protons of the imidazole ring by indirect detection through nitrogen‐15 as a function of temperature (272 K< T <293 K) and pH (1.3<pH<4.9) of uniformly nitrogen‐15‐ and carbon‐13‐labeled L ‐histidine⋅ HCl⋅ H2 O. Exchange rates up to 8.5×10 4  s −1 could be determined (i.e., lifetimes as short as 12 μs). The three chemical shifts δ Hi of the invisible exchanging protons Hi and the three one‐bond scalar coupling constants 1 J (N, Hi ) could also be determined accurately. Abstract : Seeking the invisible : The protons attached to the N atoms of histidine in an aqueous solution have hitherto escaped detection owing to the very fast exchange of these protons with the solvent. The exchange rate constants along with the one‐bond scalar couplings and chemical shifts of these elusive protons have been determined for a pH range in which the three N nuclei are protonated (see figure).